PENGARUH RASIO LIKUIDITAS, RASIO PROFITABILITAS, RASIO AKTIVITAS DAN RASIO PASAR TERHADAP RETURN SAHAM SEBELUM DAN SELAMA PANDEMI COVID-19 - Anggreni Shinta Djapalata; Sulistyo Sulistyo; Dimas Emha Amir Fikri Anas (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to examine the effect of liquidity, profitability, activity and market ratios on stock returns in the period before and during the pandemic at 17 food and beverage companies on the Indonesian Stock Exchange during the 2019-2021 period which were selected using a porpusive sampling technique. Using a descriptive quantitative approach, the data is taken from the financial reports available on the official website of the Indonesia Stock Exchange, www.idx.co.id. Investment gallery at PGRI Kanjuruhan Malang University. The data were then analyzed using multiple linear regression techniques. The results of this study show that before and during the pandemic, it is evident from the results of the study that liquidity ratios, profitability, activity and the market in general affect stock returns. However, partially, the liquidity ratio has no effect on stock returns before and during the pandemic, the profitability ratio has an effect on stock returns before and during the pandemic, the activity ratio has no effect on stock returns before the pandemic, but has an influence on stock returns. in the pre-pandemic period, and market ratios had no effect on stock returns before and during the pandemic